2020
DOI: 10.21037/apm-20-929
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lncRNA-H19/miR-140-5p in cartilage matrix degradation and calcification in osteoarthritis

Abstract: Background: To study the effect of long non-coding RNA H19/microRNA (miR)-140-5p regulatory axis on the degradation and calcification of osteoarthritis (OA) cartilage matrix.Methods: Twenty cases of clinical OA cartilage tissue and healthy cartilage tissue were collected.Construction of small interfering RNA vector (si-H19) and negative control (si-Control), miR-140-5p mimic and negative control mimic-NC, miR-140-5p inhibitor, and negative control inhibitor-NC transfected human chondrocytes HC-A cells. Chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
(16 reference statements)
1
19
0
Order By: Relevance
“…It is possible that the H19/miR-106a-5p/TCF4 axis may be responsible for the progression of OA. Yang et al 27 confirmed that silencing lncRNA H19 prevented chondrocyte apoptosis, promoted proliferation, and downregulated MMP13 levels.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that the H19/miR-106a-5p/TCF4 axis may be responsible for the progression of OA. Yang et al 27 confirmed that silencing lncRNA H19 prevented chondrocyte apoptosis, promoted proliferation, and downregulated MMP13 levels.…”
Section: Discussionmentioning
confidence: 97%
“…It is reported that the MMP family plays a primary role in progressive OA, through a critical role in the degradative regulation of cartilage matrix components (36). MMP-1 is a rate-limiting type II collagenase causing degradation and destruction of extracellular matrix and activates other MMP family members to play an essential role in OA (37). Consistent with the results of previous studies, the Hulth-induced OA rabbits showed elevated expression of BMP-2 mRNA in joint fluid, and MMP-1 expression in the articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, a prior study has revealed that miR-140-5p is essential for in vitro chondrogenesis whilst being down-regulated in osteoarthritic cartilages [ 30 ]. Moreover, miR-140-5p is indicated to protect chondrocytes from inflammatory injury during the pathogenesis of OA [ 31 ], whereas another prior investigation has uncovered that inhibition of miR-140-5p promotes the cartilage matrix degradation in OA cells [ 32 ]. Altogether, these findings and evidence indicate that OA induction inhibits miR-140-5p expression, while over-expression of miR-140-5p alleviates cartilage degradation and inflammation.…”
Section: Discussionmentioning
confidence: 99%